KRETERIA KHUSUS YANG HARUS DIPENUHI GHARIM DALAM AL-QURAN SURAT AT-TAUBAH AYAT 60 STUDI TAFSIR IBNU KATSIR - adrianto; Andriantoro; Haslinda; Chalid Sitorus (Al-Qadim - Jurnal Tafsir dan Ilmu Tafsir, 2025)
Abstract This study aims to describe Increasing how to specific criteria that must be met Gharim on Al-Qur’an at-taubah at 60 in tafsir of Ibnu Katsir the data collection technique is using library research or library study research with data collection techniques carried out by examining literature, document, and other sources of information related to the Topik of researchers. The result of this study the first,  Ibnu Katsir interpret gharim on al-quran at-Taubah at 60 such as individuals in debt due to economic hardship and unable to meet his life's needs Unable to Pay lawful debt For Basic Needs Also, things that are prohibited include: Illegal Debts from Immoral Acts Riba Gambling, online gambling debt ibnu katsir emphasizes the importance of safeguarding Permissibility of Debt The second, specific criteria that must be met gharim include; The debt is due and must be paid off immediately Debt is not due to non-urgent consumption Debt due to basic needs or for public interest the third, giving zakat to gharim those that do not meet the criteria may lead to abuse and ineffective in helping those who truly need it. where a person is not allowed to have savings or assets that can be used to pay off debts